Psychological Resilience Enhances the Orbitofrontal Network in the Elderly With Mild Cognitive Impairment - Son, Sang Joon; Park, Bumhee; Choi, Jin Wook; Roh, Hyun Woong; Kim, Na-Rae; Sin, Jae Eun; Kim, Haena; Lim, Hyun Kook; Hong, Chang Hyung (Frontiers in Psychiatry, 2019)
Background: It has been suggested that maintaining the efficient organization of the brain’s functional connectivity (FC) supports neuroflexibility under neurogenerative stress. This study examined psychological resilience-related FC in 112 older adults with mild cognitive impairment (MCI). Methods: Using a resting-state functional magnetic resonance imaging (fMRI) approach, we investigated reorganization of the orbitofrontal gyrus (OFG)/amygdala (AMG)/hippocampus (HP)/parahippocampal gyrus (PHG) FC according to the different levels of resilience scale. Results: Compared with the low resilient group, the high resilient group had greater connectivity strengths between the left inferior OFG and right superior OFG (P < 0.05, Bonferroni corrected), between the right inferior OFG and left PHG (P < 0.05, Bonferroni corrected), and between the right middle OFG and left PHG (false discovery rate < 0.05). Conclusion: Psychological resilience may be associated with enhancement of the orbitofrontal network in the elderly with MCI.